(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The article presents infographics as a method of presenting information in an accessible and engaging way. This method helps students better understand the material and simplifies the learning process. The article also explains how online platforms such as Canva, Piktochart, Venngage, Microsoft PowerPoint, Google Slides, and others can be effectively used and how infographics can assist in the learning process.